THE EXPLICIT AND ARTISTIC DISCURSIVE FORMS OF THE CONCEPT OF RESILIENCE (Ustozlar uchun, 2025)
This article analyzes the explicit and artistic discursive forms of the concept of resilience. Explicit discourse provides scientific and precise definitions, whereas artistic discourse illuminates the concept through human emotions. Both forms demonstrate complementary facets of the understanding of resilience within society and culture.